"Pulling the Parachute": A Qualitative Study of Burnout's Influence on Emergency Medicine Resident Career Choices. Issue 3 (16th October 2020) - Lu, Dave W.; Germann, Carl A.; Nelson, Sara W.; Jauregui, Joshua; Strout, Tania D.
Abstract: Objectives: About half of all resident physicians report symptoms of burnout. Burnout negatively influences multiple aspects of their education and training. How burnout may impact residents' career choices remains unclear. The authors explored the role burnout played in residents' career decisions. Methods: This was a qualitative study among a sample of 29 emergency medicine residents from four institutions. Qualitative data were generated through four semistructured focus groups. The authors employed a constructivist approach to thematic analysis. Transcripts were coded and organized into major themes. Results: Five major themes connecting burnout with residents' career choices emerged: 1) residents' current burnout and the prevention of future burnout figured prominently in their career considerations, 2) residents aimed to mitigate sources of burnout through their career choices, 3) residents' view of clinical work as a burden and a burnout contributor spurred the pursuit of other interests, 4) faculty advice and role modeling in relation to burnout shaped residents' career perspectives, and 5) residents weighed long‐term burnout concerns with short‐term financial needs. Conclusion: Burnout played an important role in multiple aspects of residents' career considerations. Educators, program directors, and organization leaders can focus on identified target areas to address burnout's influence on residents' career decisions.